The testing process: a decision based approach - Borner, Lars; Illes-Seifert, Timea; Paech, Barbara (ISCEA 2007, 2007)
Software processes often focus on artifacts, activities and roles, treating decisions to be made during the software development process only implicitly. However, awareness of these decisions increases their quality by forcing the decision-makers to search for alternatives and to trade off between them. In this paper, we propose a decision hierarchy for the testing process. This hierarchy comprises all decisions made during testing and reflects dependencies between them. Additionally, we present the results of four case studies to which we applied this decision hierarchy.